Ginseng-derived exosome-like nanovesicles extracted by sucrose gradient ultracentrifugation to inhibit osteoclast differentiation. Issue 12 (1st March 2023) - Seo, Kwansung; Yoo, Ji Hye; Kim, Jisu; Min, Sung Jun; Heo, Dong Nyoung; Kwon, Il Keun; Moon, Ho-Jin
Abstract : Ginseng-derived extracellular nanovesicles effectively blocked bone loss both in vitro and in vivo by inhibiting osteoclast differentiation through RANKL-induced IκBα, JNK, and ERK activation. Abstract : Plant-derived extracellular nanovesicles contain RNA and proteins with unique and diverse pharmacological mechanisms. The extracellular nanovesicles encapsulating plant extracts resemble exosomes as they have a round, lipid bilayer morphology. Ginseng is anti-inflammatory, anti-cancer, immunostimulant, and osteogenic/anti-osteoporotic. Here, we confirmed that ginseng-derived extracellular nanovesicles (GDNs) inhibit osteoclast differentiation and elucidated the associated molecular mechanisms. We isolated GDNs by centrifugation with a sucrose gradient. We measured their dynamic light scattering and zeta potentials and examined their morphology by transmission electron microscopy. We used bone marrow-derived macrophages (BMMs) to determine the potential cytotoxicity of GDNs and establish their ability to inhibit osteoclast differentiation. The GDNs treatment maintained high BMM viability and proliferation whilst impeding osteoclastogenesis. Tartrate-resistant acid phosphatase and F-actin staining revealed that GDNs at concentrations >1 μg mL −1 strongly hindered osteoclast differentiation. Moreover, they substantially suppressed the RANKL-induced IκBα, c-JUN n-terminal kinase, and extracellular signal-regulated kinase signaling pathways and the genes regulating osteoclast maturation. The GDNs contained elevated proportions of Rb1 and Rg1 ginsenosides and were more effective than either of them alone or in combination at inhibiting osteoclast differentiation. In vivo bone analysis via microcomputerized tomography, bone volume/total volume ratios, and bone mineral density and bone cavity measurements demonstrated the inhibitory effect of GDNs against osteoclast differentiation in lipopolysaccharide-induced bone resorption mouse models. The results of this work suggest that GDNs are anti-osteoporotic by inhibiting osteoclast differentiation and are, therefore, promising for use in the clinical prevention and treatment of bone loss diseases.